PENERAPAN UANG DIGITAL TERHADAP EFESIENSI TRANSAKSI DI SEKTOR UMKM - Armita Isnaini Munthe; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to provide an explanation of the application of digital money transactions to the efficiency of micro, small and medium enterprises (MSMEs) in Indonesia, at this point in the face of developments in financial technology, which require cloth to adapt to increase competitiveness and operational efficiency. The research method used is a qualitative approach, the same as data collection. The results show that the use of office money can make it easier to record formal transactions in the nature of payment processes, as well as reduce the risk of shortages of chemical money, namely. However, challenges such as limited understanding of technology and internet network constraints are still obstacles. Scientific studies have gathered that the implementation of digital money transactions has the potential to increase the operational efficiency of MSMEs, although there is a need for education and supporting infrastructure so that the benefits are more optimal.